Organizational practices for learning with work accidents throughout their information cycle - Silva, S.A.; Carvalho, H.; Oliveira, M.J.; Fialho, T.; Guedes Soares, C. (Safety Science, 2017)
Research has acknowledged the relevance of accident information for prevention and learning and the need for companies to develop a reporting and learning culture. Few studies have approached this issue by comparing the different learning strategies used by companies. The aim of this study is to explore how companies use accident information and to develop strategies for learning from accidents, which cover all the learning cycle phases by: (a) identifying learning patterns across company and activity sectors, (b) checking for potential differences among certified and non-certified companies. Seventeen case studies were conducted with organizations operating in different sectors in Portugal. Data was collected from extensive, semi-structured interviews with key stakeholders and an analysis of relevant documentation. All data was subjected to a descriptive analysis, followed by multivariate analysis using Multiple Correspondence Analysis (MCA). The main MCA results showed two dimensions corresponding to the technical and social learning and four patterns were found, each corresponding to different levels of learning practices ranging from the minimal practices used to a higher degree of learning, combining practices of a technical and social nature. Additionally, the results revealed that companies in the same activity sector may have very different practices, independently of OHSAS certification. The results allow us to conclude that organizations with good safety practices tend to follow the complete learning cycle. Overall, these organizations have established procedures to report accidents and to collect information on them but there are organizations that still do not maximize their means of learning from work accidents.